2022
DOI: 10.3389/fonc.2022.790933
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Profiling Reveals Biomarkers for Early Detection and Prognosis of Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common aggressive malignancies worldwide, particularly in northern China. The absence of specific early symptoms and biomarkers leads to late-stage diagnosis, while early diagnosis and risk stratification are crucial for improving overall prognosis. We performed UPLC-MS/MS on 450 ESCC patients and 588 controls consisting of a discovery group and two validation groups to identify biomarkers for early detection and prognosis. Bioinformatics and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 71 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…In our study, the processes of retinol metabolism with all-trans-13,14-dihydroretinol were significantly increased in the MS group. It has been previously reported that retinol metabolism was closely correlated with MS in adults ( 37 ), and the elevated level of all-trans-13,14-dihydroretinol was also observed in other diseases, including atherosclerosis and cancer ( 38 , 39 ). All-trans-13,14-dihydroretinol was a metabolite of retinol that was produced by retinol saturase (RetSat) ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 91%
“…In our study, the processes of retinol metabolism with all-trans-13,14-dihydroretinol were significantly increased in the MS group. It has been previously reported that retinol metabolism was closely correlated with MS in adults ( 37 ), and the elevated level of all-trans-13,14-dihydroretinol was also observed in other diseases, including atherosclerosis and cancer ( 38 , 39 ). All-trans-13,14-dihydroretinol was a metabolite of retinol that was produced by retinol saturase (RetSat) ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 91%
“…The alteration of the linoleic acid metabolism pathway has been associated with different tumor types. Altered content of membrane PCs and phospholipid (PL) profiles have also been associated with cancer development and progression. Lower plasma LPC levels have been suggested as markers of severity in cancer, including RCC with lower levels exhibited in more aggressive tumors, and increased levels in patients who were in remission 6 months after surgery . However, different trends were reported for PC 16:0 in RCC. , More studies are needed to understand how the PL metabolism is altered and regulated and to decipher the particular role of specific PLs in a pathological context.…”
Section: Resultsmentioning
confidence: 99%
“…Due to these metabolic changes, the dysregulated expression levels of these three amino acids have been previously confirmed by multiple studies as biomarkers that can be used to discriminate or predict gastric and esophageal cancers. , Unsaturated fatty acids can reduce fat accumulation and regulate blood lipids and also play an important role in immune regulation. There have been several findings supporting the notion that fatty acids are often accompanied by changes in cancer patients and are used as biomarkers to identify upper gastrointestinal cancers. Our analysis displayed a decline in the degree of unsaturation in UGI cancer patients compared with controls, which is in agreement with existing evidence. , The reduced levels of unsaturated fatty acids in upper gastrointestinal cancer patients can be attributed to the high utilization of fatty acids by active cancer cells for cell membrane synthesis and energy production. , Due to these factors, unsaturated fatty acids are significantly different between UGI cancer patients and healthy controls, suggesting their potential as biomarkers. The level of albumin serves as an indicator for assessing the nutritional status and the severity of inflammation.…”
Section: Discussionmentioning
confidence: 99%